1976
DOI: 10.1056/nejm197605272942201
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Arabinoside Therapy of Herpes Zoster in the Immunosuppressed

Abstract: We evaluated adenine arabinoside treatment of herpes zoster in immunodeficient patients in a randomized, controlled crossover study. The two study groups had similar characteristics. In spite of rapid natural healing, those receiving adenine arabinoside over the first five days had accelerated clearance of virus from vesicles (P = 0.01), and cessation of new vesicle formation (P = 0.004), and a shorter time to total pustulation (P = 0.001). Factors modifying the response to therapy included age, underlying dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1978
1978
1983
1983

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(52 citation statements)
references
References 19 publications
0
52
0
Order By: Relevance
“…Significant persisting serum AVA as a result of ara-A and ara-Hx contrasts remarkably with the transient or insignificant values which we found in patients receiving earlier candidate antiviral drugs, cytosine arabinoside and idoxuridine (8,11,22). Sustained antiherpesvirus therapeutic concentrations in human sera correlate with the salutary effects of courses of ara-A reported in patients with herpes zoster and herpes simplex virus encephalitis (2,3). Urinary excretion of parenterally administered ara-A is estimated as 52%, but the half-life of ara-A has not yet been determined by chemical studies (10).…”
Section: Resultsmentioning
confidence: 45%
See 2 more Smart Citations
“…Significant persisting serum AVA as a result of ara-A and ara-Hx contrasts remarkably with the transient or insignificant values which we found in patients receiving earlier candidate antiviral drugs, cytosine arabinoside and idoxuridine (8,11,22). Sustained antiherpesvirus therapeutic concentrations in human sera correlate with the salutary effects of courses of ara-A reported in patients with herpes zoster and herpes simplex virus encephalitis (2,3). Urinary excretion of parenterally administered ara-A is estimated as 52%, but the half-life of ara-A has not yet been determined by chemical studies (10).…”
Section: Resultsmentioning
confidence: 45%
“…Wells containing ara-A and ara-Hx also contained coara-A. After all wells were inoculated, plates were again sealed and incubated (37°C) for 48 h. 3 Unfortunately, co-ara-A was not available to add to the bloods from patients 1-9. 4 To correlate inhibition of CPE with decrements in herpes simplex virus replication as a result of ara-A or ara-Hx, the following experiments were done.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shedding of VZV had ceased in all patients by the eighth day of illness, in contrast with the findings in immunocompromised hosts. Whitley et al (1976) reported that c. 20% of immunocompromised patients with active herpes zoster shed virus up to the tenth day of illness. VZV may have cleared from the lesions more slowly in these patients because of the underlying illness, than in the otherwise normal subjects in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, most virological studies of the natural history of VZV infection have been made on very selected populations of immunosuppressed patients, and little information is available about the virological course of VZV infections in normal subjects (Gold, 1966). Some studies of the duration of virus excretion and the quantity of lesions have been reported in immunocompromised patients (Johnson et al, 1975;Whitley et al, 1976) but the results cannot be extrapolated to normal hosts. Moreover, the virological course of VZV infection in normal hosts needs careful definition, in order to design proper clinical trials of the therapeutic efficacy of antiviral drugs.…”
Section: Introductionmentioning
confidence: 99%